Understanding Vietnamese chicken farmers’ knowledge and practices related to antimicrobial resistance using an item response theory approach - Nohrborg, S.; Thinh Nguyen-Thi; Huyen Nguyen Xuan; Lindahl, Johanna F.; Boqvist, S.; Järhult, J.D.; Magnusson, U. (Frontiers Media, 2024)
Introduction: Antimicrobial resistance (AMR) poses a threat to animal and human health, as well as food security and nutrition. Development of AMR is accelerated by over- and misuse of antimicrobials as seen in many livestock systems, including poultry production. In Vietnam, high AMR levels have been reported previously within poultry production, a sector which is dominated by small-scale farming, even though it is intensifying. This study focuses on understanding small- and medium-scale chicken farmers’ knowledge and practices related to AMR by applying an item response theory (IRT) approach, which has several advantages over simpler statistical methods.